2015
DOI: 10.18632/oncotarget.4136
|View full text |Cite
|
Sign up to set email alerts
|

AF1q is a novel TCF7 co-factor which activates CD44 and promotes breast cancer metastasis

Abstract: AF1q is an MLL fusion partner that was identified from acute myeloid leukemia (AML) patients with t (1; 11) (q21; q23) chromosomal abnormality. The function of AF1q is not yet fully known, however, elevated AF1q expression is associated with poor clinical outcomes in various malignancies. Here, we show that AF1q specifically binds to T-cell-factor-7 (TCF7) in the Wnt signaling pathway and results in transcriptional activation of CD44 as well as multiple downstream targets of the TCF7/LEF1. In addition, enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 45 publications
10
55
0
Order By: Relevance
“…It was reported that AF1q enhanced Wnt signaling pathway by interacting with TCF7 to activate CD44 transcription [15]. We further confirmed the interactions between AF1q and TCF7.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…It was reported that AF1q enhanced Wnt signaling pathway by interacting with TCF7 to activate CD44 transcription [15]. We further confirmed the interactions between AF1q and TCF7.…”
Section: Resultssupporting
confidence: 85%
“…However, this effect may be indirect because we found that AF1q specifically binds to TCF7. It was demonstrated that AF1q promotes transcriptional rates through increasing the formation of transcriptional complex with lymphoid enhancer-binding factor (LEF) and β-catenin [15]. Additionally, we found that TCF7 transcriptional level was also increased by AF1q.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The consensus today is that AF1q plays an important role in malignancy of solid tumors, but the molecular mechanisms by which AF1q interacts with oncoproteins or influences tumor suppressor gene loss are incompletely understood. We previously demonstrated that AF1q physically interacts with the HMG box protein TCF7, a key factor in Wnt signaling, and AF1q enhances expression of Wnt target genes [26]. The AF1q-TCF7 interaction results in enhanced expression of CD44, a ubiquitous multi-structural and multi-functional cell surface glycoprotein involved in adhesion, migration, and homing of cells.…”
Section: Introductionmentioning
confidence: 99%